(untitled) (Studia Prawnicze / The Legal Studies, 1981)
This article presents the legal principles of legalisation of religious associatiuns in Poland. Due to the lack of an uniform regulation and to many changes this regulation has underwent, the problem of legalisation of religious associations is a very complex one. Some of the said associations are operating on the basis of laws issued in the times of the IInd Commonwealth. Through this mean however only 6 of the religious associations were legalised. During the first few years after the IInd World War the same procedure of legalisation was followed, soon to be replaced by administrative decisions taken by the Secretary of Public Administration. This change of procedure has resulted from practical activities of administration rather than from a legal norms. In 1949, as a result of changes in the legal regulation concerning the activities of associations, the religious associations were covered by this new regulation. This change, however, has not led to the creation of an uniform regulation in this subject. According to the law of associations a religious association can operate as an ordinary association (and thus be active on local area) or as a registered association (and thus operating over the whole area of the country). The next part of the article deals with problems of delegalisation of the religious association, with the refusal of legalisation and legal reasons for such a decision. The article ends with proposals aiming at the creation of an uniform regulation dealing with the mentioned problems.